2019
DOI: 10.3390/molecules24061139
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Colonic Immune Function with Soy Isoflavones in High-Fat Diet-Induced Obese Rats

Abstract: Background: The damage to intestinal barrier function plays an important role in the development of obesity and associated diseases. Soy isoflavones are effective natural active components for controlling obesity and reducing the level of blood lipid. Here, we explored whether these effects of soy isoflavones were associated with the intestinal barrier function. Methods and Results: The obese rat models were established by high fat diet feeding. Then, those obese rats were supplemented with soy isoflavones at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 66 publications
3
56
0
Order By: Relevance
“…Likewise, olive oil supplements improved the severity of dextran sulfate sodium-induced colitis in mice [ 66 ]. Furthermore, evidence showed that complement of soy isoflavones improved intestinal permeability, lowered serum lipid, inhibited inflammatory response, and corrected intestinal microbiota imbalance of obese rats [ 67 ].…”
Section: Dyslipidemia Accelerates Colitis-associated Crcmentioning
confidence: 99%
“…Likewise, olive oil supplements improved the severity of dextran sulfate sodium-induced colitis in mice [ 66 ]. Furthermore, evidence showed that complement of soy isoflavones improved intestinal permeability, lowered serum lipid, inhibited inflammatory response, and corrected intestinal microbiota imbalance of obese rats [ 67 ].…”
Section: Dyslipidemia Accelerates Colitis-associated Crcmentioning
confidence: 99%
“…For example, the study of Luo et al show that soy isoflavones decrease food intake and body weight gain in mice [18]. Moreover, soy isoflavones can regulate lipid metabolism through AKT/mTORC1 pathway [19] and improve the colonic immune function in obese rats induced by high-fat diet [20]. However, the effects of soy isoflavones on hypothalamus under obesity condition are not well defined, especially describing this from oxidative stress aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly higher food consumption was recorded in three studies [2-PPC [ 41 , 50 ], 1-PE [ 73 ], while 24 studies reported non-significant difference in energy/food intake [ 45 , 46 , 47 , 51 , 52 , 57 , 59 , 60 , 62 , 63 , 66 , 74 , 75 , 80 ] ( Figure S4 ). As for bodyweight, thirty studies (67%) recorded a significant drop post-treatment, of which 16 with PPC [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 50 , 52 , 53 , 54 , 56 , 57 ], and 15 with PE [ 60 , 61 , 63 , 65 , 66 , 68 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 81 ]. Non-significant observations were made in 19 studies [11-PPC [ 37 ...…”
Section: Resultsmentioning
confidence: 99%